Parametric analysis of presession exposure to edible and nonedible stimuli - Sy, Jolene R.; Borrero, John C. (Wiley Online Library, 2009)
We assessed the effects of individually defined small, medium, and large periods of presession access to edible and nonedible reinforcers on response rates during sessions in which responding produced access to identical reinforcers. Any presession access to an edible reinforcer decreased response rates for 1 participant, and small and medium periods of presession access to nonedible reinforcers resulted in similar or increased response rates for 2 participants.
Keywords: establishing operations; parametric evaluation; presession access; reinforcer efficacy